A whole systems view to driving decentralised renewable energy investments in Sub-Saharan Africa. - Abba, Yahajja Zara Ibrahim (Cranfield University, 2024)
The scaling-up of decentralised renewable energy (DRE), such as solar mini- grids, is vital to achieving climate goals and universal electricity access in sub- Saharan African (SSA) countries. However, high investor risk perception continues to impede DRE investment in SSA, highlighting the importance of understanding investors' risk perception and developing appropriate risk mitigation actions. Yet, the risk management (RM) literature offers a fragmented and singular approach, where the multidimensional nature of risk factors and their interactions are overlooked. In addition, current studies do not consider DRE site- specificity alongside investor heterogeneity in quantifying the implications of mitigation actions on the evolution of investment decisions. In this context, and to address these research gaps, this thesis aims to develop, validate, and implement a unified RM framework incorporating an investment decision model to assess the impacts of actions on investment and electricity access spatially, thus offering a more holistic outcome for decision-makers. This thesis focuses on solar mini-grids in Nigeria, which has one of the highest electricity deficits in SSA. The framework is implemented in two phases. In phase one, investment risks and potential mitigations were evaluated as perceived by four investor groups and various stakeholders through questionnaires, semi-structured interviews, focus groups, and an analytic hierarchy process methodology. In phase two, a novel DRE decision-support model was deployed to enhance existing methods by using a system dynamics-agent-based modelling (SD-ABM) approach. This approach incorporates complex interactions and feedback between heterogeneous investor and location attributes to establish investment outcomes for various case study mitigation scenarios. This thesis the following contributions. Phase one provides new empirical data comprising: identifying 13 additional risk factors compared to the literature, establishing importance of risk factors as perceived by diverse investor groups in Nigeria, and proposing mitigation strategies, some of which were tested in phase two as scenarios. The results indicated variations in risk importance among investors, with the most critical risk factors being revenue risks, limited access to low-cost capital, currency risks, insecurity, and inadequate policy implementation. Phase two contributes to the knowledge of how complex system modelling can be applied to evaluate the impact of mitigation actions on the spatial evolution of DRE investment in a liberalised market. The case study results revealed that the most impactful mitigation scenarios were increased funding availability and the implementation of renewable energy mandates for domestic finance institutions. Whilst our findings confirm the criticality of concessional investors as identified in the literature, we find that meeting electrification targets necessitates incentivising risk-averse non-concessional-type investors. The developed model can additionally enable policymakers to explore the potential implications of further policy actions and investors to identify potential projects that suit their investment profiles during the feasibility phase.
Drew, Gill - Associate Supervisor
Keywords: Investment risk management; agent-based modelling; system dynamics; Investment decision support; risk evaluation; risk mitigation